Factors Associated with Gastritis Symptoms in High School Adolescents - Azizah, Azizah; Purba, Chandra Isabella Hostanida; Sari, Sheizi Prista (Indonesian Journal of Global Health Research, 2024)
Gastritis is an inflammatory process of the gastric mucosa and submucosa that, if not treated immediately, can lead to very dangerous complications. Adolescents often do not pay attention to their health because they are busy with school activities. This makes adolescents vulnerable to gastritis symptoms. Symptoms of gastritis that often appear include burning in the stomach, decreased appetite, heartburn, nausea, vomiting, bloating, and frequent burping. Factors causing gastritis include diet, age, knowledge, medications, stress, and bacteria. Objective: identify factors associated with gastritis symptoms in adolescents. Method: This study used a descriptive correlation research design using a cross-sectional approach. The population of this study was all first-grade and second-grade students in high school; the sample used totaled 112 students, and the sampling technique used was proportionate stratified random sampling. Data analysis in this study used univariate and bivariate analyses. The form of univariate analysis in this study is in the form of distribution and percentage, while the bivariate analysis uses the Chi-square test. Results: The results showed that adolescents in high school who experienced gastritis symptoms were 48 respondents (42.9%). Correlation test between age and gastritis symptoms obtained p-value 0.000, gender with gastritis symptoms obtained p-value 0.022, diet with gastritis symptoms obtained p-value 0.032, stress with gastritis symptoms obtained p-value 0.003, consumption of NSAID drugs with gastritis symptoms obtained p-value 0.000, and smoking with gastritis symptoms obtained p-value 0.246. Conclusions: Factors associated with gastritis symptoms in adolescents in high school include age, gender, diet, stress, and consumption of NSAIDs. As for smoking, it was not associated with gastritis symptoms in adolescents in high school.